EFEKTIVITAS Plant Growth Promoting Rhizobacteria (PGPR) DAN Pseudomonas fluorescens DALAM MENGHAMBAT PENYAKIT BUSUK LUNAK PADA TANAMAN KUBIS BUNGA (Brassica oleraceavar. botrytis L) - Risma Mandang; Berty Assa; Denny S. Sualang (Universitas Sam Ratulangi, 2016)
ABSTRACTThe aims of this research were to find the effectiveness of PGPR and P. fluorescens inpreventing wet rot that caused by E. carotovora. This research was conducted in VillagePaslaten, Tomohon city. The research was conducted in three places, namely The Laboratoryof Plant food and Horticulture of Protection North Sulawesi Province, cauliflower plantinglocation in Tomohon and the laboratory of Microbiology and Plant Pathology Faculty ofAgriculture Unsrat Manado. This research used RCBD with 4 treatments and 6 repetitions.Observation was done in 6 times and the time interval was one week. The result of the studyshowed several symptoms that happened to the cauliflowers, they were: the leaves wereblackish brown, shrank and looked pale, and also the small wet symptom sections becomewiden quickly. The infected soft produced a bad oder. This research showed the impact ofcollaborated treatment of PGPR and P. fluorescens was more effective since it showed ansignification different from giving PGPR or P. fluorescens separately that did not show anyimpact. The result of isolation showed that the bacteria which caused the wet rot in plantcauliflower in Tomohon was bacteria Erwinia Carotovora looking form its characteristic,creamy white colonies, slimy, shiny, convex and looked flat.Keyword: Effectiveness, Cauliflower, Soft root, Erwinia carotovora, Plant GrowthPromoting Rhizobacteria, Pseudomonas fluorescens.